EDUKASI DIGITAL MARKETING BERBASIS APLIKASI TIK TOK BAGI PELAKU UMKM DI DESA SUKA RAMI, KECAMATAN AIR NIPIS, KABUPATEN BENGKULU SELATAN - Feldi Rahman; Desi Isnaini; Andi Harpepen (JSE: Jurnal Sharia Economica, 2026)
This community service program aims to improve the digital marketing capabilities of MSME actors through the utilization of the Tik Tok application as a product promotion medium in Suka Rami Village, Air Nipis District, South Bengkulu Regency. The activity was motivated by the limited marketing methods used by MSMEs, which still relied on conventional promotion, resulting in limited market reach. The method used in this program was Asset Based Community Development (ABCD), consisting of asset identification, observation, socialization, training, mentoring, and evaluation stages. The materials provided included digital marketing concepts, content marketing, product photo and video creation techniques, video editing using the CapCut application, and promotional strategies through Tik Tok. The results of the program showed an improvement in the understanding and skills of MSME actors in creating business accounts, producing attractive promotional content, editing videos, and independently uploading promotional content on social media. The utilization of Tik Tok provides opportunities for MSME actors to expand market reach, strengthen product branding, and support sustainable business development